2022
DOI: 10.1111/jen.13086
|View full text |Cite
|
Sign up to set email alerts
|

Updating new invasions: The Australian tortoise beetle Trachymela sloanei (Blackburn, 1897) (Coleoptera: Chrysomelidae) in the Iberian Peninsula

Abstract: Trachymela sloanei (Blackburn, 1897) is a non‐indigenous beetle of the Iberian Peninsula herbivorous of several species of Eucalyptus trees. Since its first detection in Europe in 2014, little information is available about the populations of this beetle in this distribution range. Therefore, a complete chorological update of the Australian tortoise beetle in the Iberian Peninsula is carried out. The ecology, phenology and potential distribution are discussed. Certain features of its morphology are fully illus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
12
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(12 citation statements)
references
References 19 publications
(29 reference statements)
0
12
0
Order By: Relevance
“…(c) Negative (red circles) and positive (yellow symbols, triangles: trees monitored the whole study period, circles: trees monitored during June–July) records of T. sloanei on Eucalyptus trees in Campo de Tabernas (Almería), whose location is marked by a rectangle in (1b). Green circles are positive records reported in Pérez‐Gómez et al (2022). See Methods section for further details.…”
Section: Methodsmentioning
confidence: 80%
See 4 more Smart Citations
“…(c) Negative (red circles) and positive (yellow symbols, triangles: trees monitored the whole study period, circles: trees monitored during June–July) records of T. sloanei on Eucalyptus trees in Campo de Tabernas (Almería), whose location is marked by a rectangle in (1b). Green circles are positive records reported in Pérez‐Gómez et al (2022). See Methods section for further details.…”
Section: Methodsmentioning
confidence: 80%
“…However, the species was not found behind nest boxes placed elsewhere (other tree species, cliffs or farmhouses) (but see Pérez-Gómez et al, 2022), nor pupae were ever observed behind or in the nest boxes. We found a similar probability of detection of the species behind trees and bark, although future studies with a larger sample size would be desirable.…”
Section: Discussionmentioning
confidence: 91%
See 3 more Smart Citations